2020
DOI: 10.1039/c9sc05114g
|View full text |Cite
|
Sign up to set email alerts
|

Imaging effects of hyperosmolality on individual tricellular junctions

Abstract: A nanoscale electrochemical imaging method was used to reveal heterogeneity present in conductance at epithelial cell junctions under hyperosmotic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Perspiration-induced dehydration produces a decrease in plasma volume and extracellular water which leads to hyperosmolarity. Hyperosmolarity has been reported to enhance paracellular permeability in Caco-2 cells without damaging the cell membranes via cell shrinkage 51 and/or via hyperosmolar driven disruption of tight junctions 52 . This could explain the observed increase in intestinal permeability without intestinal damage in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Perspiration-induced dehydration produces a decrease in plasma volume and extracellular water which leads to hyperosmolarity. Hyperosmolarity has been reported to enhance paracellular permeability in Caco-2 cells without damaging the cell membranes via cell shrinkage 51 and/or via hyperosmolar driven disruption of tight junctions 52 . This could explain the observed increase in intestinal permeability without intestinal damage in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol is a hyperosmolar agent used in the treatment of brain trauma and is widely known to diminish the barrier function of the BBB. [ 65–67 ] Mannitol was introduced at the apical side of the BBB model and a clear decrease of the TEER value was observed (Figure 5d). After 90 min of mannitol treatment, the TEER value dropped by ≈40% of the original value, showing the paper/nanofiber‐based BBB model mimics observations for in vivo BBB to hyperosmotic conditions.…”
Section: Resultsmentioning
confidence: 96%
“…In the central nervous system of mammals, the BBB is created at the level of the endothelial brain cells, where multiple protein complexes accumulate at the cell-junctions, restricting the paracellular diffusion of ions and other polar solutes, hence effectively blocking the penetration of macromolecules. Unfortunately, therapeutic hyperosmolar agents can reversibly open thigh junctions in the cerebrovascular endothelium, and their conductivity depends on the degree of plasma hyperosmolality [ 87 , 88 , 89 , 90 ]. An experimental study has shown a temporal induction of neuroinflammatory response following intracarotid infusion of mannitol [ 89 ].…”
Section: Plasma Hyperosmolality and The Blood–brain Barriermentioning
confidence: 99%